Patterns of presentation and clinical features of toxicity after reported use of ([2-aminopropyl]-2, 3-dihydrobenzofurans), the 'benzofuran' compounds. A report from the United Kingdom National Poisons Information Service. (December 2014) - Kamour, Ashraf; James, David; Lupton, David J.; Cooper, Gillian; Eddleston, Micheal; Vale, Allister; Thompson, John P.; Thanacoody, Ruben; Hill, Simon L.; Thomas, Simon H. L.
Abstract Objective. To characterise the patterns of presentation and clinical features of toxicity following reported recreational use of benzofuran compounds ((2-aminopropyl)-2, 3-dihydrobenzofurans) in the UK, as reported to the National Poisons Information Service (NPIS), and to compare clinical features of toxicity with those after reported mephedrone use. Methods. NPIS patient-specific telephone enquiries and user sessions for TOXBASE®, the NPIS online information database, related to (2-aminopropyl)-2, 3-dihydrobenzofurans and associated synonyms were reviewed from March 2009 to August 2013. These data were compared with those of mephedrone, the recreational substance most frequently reported to NPIS, collected over the same period. Results. There were 63 telephone enquiries concerning 66 patients and 806 TOXBASE® user sessions regarding benzofuran compounds during the period of study. The first telephone enquiry was made in July 2010 and the highest numbers of enquiries were received in August 2010 (33 calls, 112 TOXBASE® sessions). Patients were predominantly male (82%) with a median age of 29 years; 9 reported co-ingestion of other substances. Comparing the 57 patients who reported ingesting benzofuran compounds alone with 315 patients ingesting mephedrone alone, benzofurans were more often associated with stimulant features, including tachycardia, hypertension, mydriasis, palpitation, fever, increased sweating, and tremor, (72% vs. 38%, odds ratio [OR] 4.2, 95% confidence interval [CI] 2.27–7.85, P < 0.0001) and mental health disturbances (58% vs. 38%, OR 2.3, 95% CI 1.29–4.07, P = 0.006). Other features reported after benzofuran compound ingestion included gastrointestinal symptoms (16%), reduced level of consciousness (9%), chest pain (7%), and creatinine kinase elevation (5%). Conclusions. Reported ingestion of benzofuran compounds is associated with similar toxic effects to those of amphetamines and cathinones. Mental health disturbances and stimulant features were reported more frequently following reported ingestion of benzofuran compounds than after ingestion of mephedrone.